Patients with intellectual disabilities in the forensic asylums 1915–1982: before admission - Erik Søndenaa; Camilla Gudde; Øyvind Thomassen (Scandinavian Journal of Disability Research, 2014)
Until 1982, a number of patients with intellectual disabilities (ID) in Norway were hospitalized in the country's two forensic mental health hospitals. The aim of this article was to explore the background of these patients based on the characteristics of their life experiences before admission to the hospital. Data from the period 1895–1982 were retrieved for 272 patients with ID. All patients' records were read and key information from childhood and important life experiences were categorized in terms of both numeric and descriptive variables. Most patients had experienced social and health problems in their family during childhood. A minority had completed primary education. A majority of the patients had some work experience. Offences leading to admission included several types from simple to serious crimes. Three periods were compared in order to study the changes in relation to the changing social and welfare conditions during the century. One main observation was that in spite of better education the trend during the century was that fewer of these patients experienced any labour participation. Historically, the diversity in level of functioning and previous treatment makes patients with ID in the forensic mental health hospitals a more varied group than previously described.